2015
DOI: 10.1021/acs.orglett.5b00886
|View full text |Cite
|
Sign up to set email alerts
|

Acetonitrile as a Cyanating Reagent: Cu-Catalyzed Cyanation of Arenes

Abstract: A novel approach to the Cu-catalyzed cyanation of simple arenes using acetonitrile as an attractive cyano source has been documented. The C-H functionalization of arenes without directing groups involves a sequential iodination/cyanation to give the desired aromatic nitriles in good yields. A highly efficient Cu/TEMPO system for acetonitrile C-CN bond cleavage has been discovered. TEMPO is used as a cheap oxidant and enables the reaction to be catalytic in copper. Moreover, TEMPOCH2CN 6 has been identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). An examination of the substituent effects in aryl alkenes showed that neither electron-withdrawing nor -donating groups had an obvious impact on the yields.A variety of functional groups were tolerated, such as ether, ester,k etone,c hloride,b romide,i odide,b oronic acid ester, and amide groups.The compatibility of this reaction with the reactive functional groups,i ncluding bromide (4-14, 4-15, 4-24), iodide (4-16), and boronic acid ester (4-12), allowed further CÀCc oupling transformations.T he HCF 2 /CN-containing estrone derivatives were synthesized by this cyanodifluoromethylation conversion, further demonstrating the synthetic utility of this method (4)(5)(6)(7)(8)…”
mentioning
confidence: 91%
“…Because ac opper source is usually required in cyanotrifluoromethylation of alkenes, [13] various Cu complexes were examined (entries 1-4) and CuI was found to be as uperior choice (entry 1). Other nitrogen sources for the nitrile group were screened (entries [15][16][17][18][19], and ammonia (NH 3 )w as also an efficient source (entry 15). A7 8% yield was obtained when 3equivalents of NaNH 2 (entry 9) were used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They obtained yields from 41% to 88%, and the reaction showed good functional group tolerance . Finally, there are further cyanation sources, eg, acetonitrile, or (ethoxy‐methylene)cyanoacetate, mentioned in the recent 12 C‐carbon literature; however, these provide less benefit for isotope science due to the necessity to produce the cyanation reagent first from 14 C‐KCN and their needing a stoichiometric excess which is unfavorable for labelling applications.…”
Section: Cyano‐group Sourcesmentioning
confidence: 99%
“…Requirement of elevated temperatures (150–250 °C) being another shortcoming of those processes. One of the practical solutions that has emerged to reduce the risk of hazardous metal cyanides, is to employ, either non‐metallic cyanide sources, such as aryl(cyano)‐iodonium triflates, acetone cyanohydrin, malononitrile, AIBN, benzyl cyanide, acetonitrile, butyronitrile, ethyl (ethoxymethylene)cyanoacetate, etc., or sources which can generate CN – group in situ (indirect sources). Recent examples of such “indirect sources” are nitromethane, the combination of NH 4 I‐DMF, NH 4 HCO 3 ‐DMSO or NH 4 HCO 3 ‐DMF, DMF and t BuNC…”
Section: Introductionmentioning
confidence: 99%